2011
DOI: 10.4049/jimmunol.1002090
|View full text |Cite
|
Sign up to set email alerts
|

Protective B Cell Responses to Flu—No Fluke!

Abstract: The mechanisms regulating the induction and maintenance of B lymphocytes have been delineated extensively in immunization studies using proteins and hapten-carrier systems. Increasing evidence suggests, however, that the regulation of B cell responses induced by infections is far more complex. Here we review the current understanding of B cell responses induced following infection with influenza virus, a small RNA virus that causes “the flu”. Notably, the rapidly induced, highly protective and long-lived humor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
83
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(87 citation statements)
references
References 77 publications
(115 reference statements)
2
83
0
2
Order By: Relevance
“…Another distinguishing feature of GLA-SE is its ability to amplify a Th1 CD4 T-cell response; animals immunized with GLA-SE produced >30-fold more IFN-γ + CD4 T cells than the number of IL-5 + CD4 T cells stimulated with SE, which led to a significant IgG1 to IgG2c shift in antibody expression. Mechanistically, antibody responses are critical for anti-influenza protection (23,24). Consistent with this fact, we showed that B cells were required for rH5-induced protection and that conditions that increased antibody production improved recovery from infection.…”
Section: Discussionsupporting
confidence: 66%
“…Another distinguishing feature of GLA-SE is its ability to amplify a Th1 CD4 T-cell response; animals immunized with GLA-SE produced >30-fold more IFN-γ + CD4 T cells than the number of IL-5 + CD4 T cells stimulated with SE, which led to a significant IgG1 to IgG2c shift in antibody expression. Mechanistically, antibody responses are critical for anti-influenza protection (23,24). Consistent with this fact, we showed that B cells were required for rH5-induced protection and that conditions that increased antibody production improved recovery from infection.…”
Section: Discussionsupporting
confidence: 66%
“…This facilitates viral evasion of the longterm control of infection by neutralising antibodies. 15 With antigenic drift, although the variant differs from the parent virus, this difference is sufficiently small that existing antibody to the parent virus is able to provide some, albeit incomplete protection. Nevertheless, the novel variant now becomes the predominant strain.…”
Section: Disease Impactmentioning
confidence: 99%
“…Previous studies showed that peritoneal B-1a cells can migrate to the spleen (36,37) and that those present in the pleural cavity can migrate to mediastinal lymph nodes (38). To determine whether the peritoneal B-1a subsets differ in their migratory potential, we adoptively transferred equal numbers of sort-purified subsets i.p.…”
Section: Pc1mentioning
confidence: 99%